MAPPING THE IRANIAN ISI PAPERS ON NANOSCIENCE AND NANOTECHNOLOGY: A CITATION ANALYSIS APPROACH - Baradar, Roya; Tajdaran, Mansour; Seyed, Majid Musavi; Abedi, Hoda (Malaysian Journal of Library and Information Science, 2009)
To clarify the interdisciplinary relationships of Iranian ISI papers on nanoscience and nanotechnology (N&N) and scheme its development pattern, a detailed citation analysis study was conducted. An increasing trend of publications from 1 paper in 1995 (with 26 citations) to 94 papers in 2007 (with 2425 citations) is obtained. With about 90%, journal papers have the most impacts on the N&N citations. Citation to books after 2003 is an indicative of N&N evolution. To the end of 2007, 14 different subject fields containing 25 disciplines contribute in the foundations of N&N. The 4 top subject fields in N&N are manufacturing and transport engineering (with 48.5% of all citations), physical sciences (15%), chemical sciences (14.7%), and nano (13.3%). Alternatively, metallurgy (with 28.01%), physic (17.33%) and materials engineering (16.48%) appear as the top three disciplines. In general, the standard deviations of the data are fairly large, indicating considerable variability among them. While N&N in Iran is a multidisciplinary field, the dynamic nature of nano causes to afford sources itself gradually. Besides, it is inevitable that novel nano sources enter in other fields in the future. In other words, the relationships among N&N and other disciplines appear mutually. Finally, in the outlining perspectives of N&N in Iran, the convergence of basic sciences (physics and chemistry) and engineering (materials engineering and metallurgy) have the highest impacts on their fundamental and applied aspects, respectively.